Dynamics of the continental slope demersal fish community in the Colombian Caribbean – Deep-sea research in the Caribbean (2015)
Abstract: Nowadays, the limited knowledge of marine biodiversity in the deep-sea faces increasing human exploration interest of this environment in the Colombian Caribbean (e.g. recent hydrocarbon exploration activities), wich makes it a national problem. This scenario requires a better understanding of the biodiversity, ecology, and biogeography of species that live in the territorial and adjacent waters of Colombia towards an adequate management of resources. The deep-sea demersal fish community is one of the main faunal groups that can be used to track aggregations of biodiversity in deep-sea ecosystems. The deep-sea waters of the Colombian Caribbean have been investigated by some foreign and national expeditions during the last five decades. Since then, the information obtained has been stored in a wide array of cruise reports and “gray” literature. With the main goal of identifying aggregations of biodiversity in terms of deep-sea fish species numbers and the physical and biological factors that may cause certain spatial distribution patterns. The current thesis summarizes the available information to produce a comprehensive inventory of demersal deep-sea fishes present in the Colombian Caribbean. Their structural patterns are analyzed in terms of composition and distribution through a multivariate regression tree (MRT) analysis to identify different environmental factors that may be influencing fish distributions. Hypotheses of correlation between the distributional patterns and the bathymetric (200 to 980 m), geographic (east-west), and topographic (bottom landscape) ranges are tested. A spatial analysis of the number of species per station under the light of the available environmental information and recent findings of deep-sea ecosystems in Colombia was made as well. As a result of this, 343 species of deep-sea demersal fishes included in 26 orders and 92 families are identified for the Colombian Caribbean. Six fish assemblages were found in the continental slope mainly characterized by depth and geographical location. Based on the outcomes of the spatial analyses, three areas of aggregations of biodiversity of fish fauna were identified between 300 and 500 m depth in the Colombian Caribbean continental waters and one on insular waters. The continental offshore areas identified are located close to the sites where deep-sea reef ecosystems were reported before.The results support the idea of the Caribbean territorial waters of Colombia as an area with high values of deep-sea fish species compared to other regions in the western Atlantic coast. The structural data suggest a northeastern region that shows the highest concentration of species richness and abundances between the lower part of the upper slope and the upper part of the middle slope (275 – 602 m). Finally, the aggregations of fishes found add support to the previous stated evidence of the presence of deep-sea reefs ecosystems in the Colombian Caribbean located between the continental shelf break and the middle slope.